Effectiveness Of Hospital Management Information System (SIMRS) On The Efficiency Of Outpatient Services - Syaiful Bachri; Rezqiqah Aulia Rahmat (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Hospital Management Information System (SIMRS) is an important component in improving the efficiency of health services, especially outpatient services. This study aims to determine the effectiveness of SIMRS implementation on the efficiency of outpatient services at Hospital X. The study used an analytical quantitative design with a cross-sectional approach. The study sample consisted of 60 respondents consisting of registration officers, nurses, and administrative staff. Data were collected using a questionnaire and analyzed using the Chi- Square test. The results showed a p value = 0.003 (<0.05) which means there is a significant relationship between SIMRS implementation and outpatient service efficiency. SIMRS has been proven effective in accelerating service time, increasing data accuracy, and reducing administrative errors.